IMPLEMENTASI BUKU PEDOMAN KARAKTER SEBAGAI UPAYA MENUMBUHKAN RASA TOLERANSI BERBASIS NILAI RELIGIUS PADA SISWA SEKOLAH DASAR - Melik Budiarti; Pinkan Amita Tri; Octarina Hidayatus Sholikhah (Universitas Muhammadiyah Ponorogo, 2019)
The Character Guidebook is a reference book for elementary school age children that aims to foster a sense of tolerance and love for the Republic of Indonesia. This study aims to implement a character manual developed by the research team. The study involved 25 and accompanying teachers at SDN Taman 4 Madiun. Data validation or data validity refers to data triangulation methods including source triangulation, methods and researchers. Data analysis techniques in this study refer to the interactive models of Miles and Hubermen which include: 1) data collection, 2) data reduction, 3) data presentation, 4) conclusion drawing. The results of implementation with the role of the character manual, character building to foster a sense of tolerance have a positive impact. Through the use of the character manual, it is hoped that it can become a guideline for teachers and students to apply the character, especially the sense of tolerance that is applied as a support for learning in school.